The Second Mile for Legal Aid Clinics - John S. Bradway (Washington University Law Quarterly, 1952)
The current Survey of the Legal Profession has produced many interesting and valuable reports. One of these, prepared by Professor Quintin Johnstone, deals with “Law School Legal Aid Clinics.” The report makes clear that the legal aid clinic movement, which is designed to meet one of the major criticisms directed against modern legal education, is rapidly approaching maturity. It is not the purpose of the present article to supply a reprint of Professor Johnstone's report. That compilation of data should be read in its entirety and appreciated on its own substantial merits. However, reference may be made to three items appearing in it. It suggests a definition of legal aid clinic work, “a law school sponsored program for law student work on legal aid cases.”
Keywords: Public legal service; Legal aid